Measurement and evaluation of emergency lighting equipped with LED - Baleja, Richard; Novák, Tomáš; Sokanský, Karel (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
The issue of emergency lighting is quite complicated and meeting all standard requirements are often very complex. Rapid development in the field of LED light sources has brought new possibilities in the design of emergency lighting. In particular, LED has a higher power output in comparison to conventional light sources used in emergency lighting and also the size of LED is smaller. Another advantage is the possibility of optimal routing of LED diodes by means of suitable optics depending on the areas and the type of emergency lighting. Measurements were performed on a prototype of autonomous emergency lamp, which does not use a conventional battery as a source of energy, but super-capacitor. Especially from the perspective of a long lifespan, its fast charging and reducing of dependence on temperature, the super-capacitor seems like very reliable replacement of batteries previously used.
Měření a vyhodnocení nouzového osvětlení osazeného LED
Keywords: super-capacitor; emergency lighting; power LED diode.